Analisis risiko pembiayaan dalam bank syariah dan upaya mitigasinya: Praktik di Indonesia - Rushady, Fijar Rahmawan (Maliki Interdisciplinary Journal, 2026)
This study aims to comprehensively examine financing risk in Islamic financial institutions in Indonesia as well as various approaches to mitigate it based on Islamic risk management principles. Employing a qualitative approach through literature review, this research explores the distinctive characteristics of financing risk across various sharia contracts, the variables influencing the level of non-performing financing (NPF), and the effectiveness of preventive and remedial measures implemented. The findings indicate that financing risk in Islamic banking is influenced by sectoral concentration of fund disbursement, macroeconomic conditions such as inflation and the pandemic period, and the extent to which institutions apply the 5C principle analysis and portfolio diversification. The countercyclical policy stipulated in POJK 11/POJK.03/2020 has proven effective in suppressing NPF rates through restructuring schemes. The latest regulations issued by the Financial Services Authority (OJK), namely POJK 20/2025 and POJK 21/2025, which refer to international standards such as Basel III and IFSB, further strengthen the liquidity resilience and capital structure of Islamic banks. Recommendations from this study include the development of a digital-based early warning system, sectoral diversification, and enhancement of human resource competence in integrated risk management.